Predictors of Instrumental Activities of Daily Living Performance in Patients with Stroke - Amin Ghaffari; Hamid Reza Rostami; Malahat Akbarfahimi (Occupational Therapy International)
Objective. Instrumental activities of daily livings are important for independent living and active participation in the community. The present study is aimed at determining factors predicting instrumental activities of daily living performance in patients with stroke. Methods. In this cross-sectional study, a convenient sample of 90 patients with stroke entered from five occupational therapy centers, which were selected based on the cluster randomization method. Lawton IADL scale, Barthel Index, Trail Making Test (A and B), Digit span subtest of Wechsler memory scale, Motorcity index, and Beck Depression Inventory-II were used to investigate the study’s aim. Statistical analyses were performed using independent sample t-test, one-way ANOVA, Pearson correlation, and multiple linear regression analysis. Results. Age (r=−0.384, p<0.001), memory (r=0.565, p<0.001), basic activities of daily living (r=0.818, p<0.001), depression (r=−0.758, p<0.001), Trial Making Test (B-A) (r=−0.614, p<0.001), and motoricity index (r=0.670, p<0.001) were significantly associated with instrumental activities of daily living performance. Conclusions. Basic activities of daily living were the strongest predictor of IADL’s performance. Age, TMT (B-A), and depression were orderly the next strongest predictors. Stroke patients with more dependency in basic activities of daily living, older age, cognitive impairment, and depression are more opted to be dependent in instrumental activities of daily living and as a result, less participation in home and community affairs.